Bibliometric analysis of scientific production on gamification in History teaching - Farias, Natália Silva (2023)
Gamification has become increasingly popular as a pedagogical strategy in several areas of knowledge. This approach consists of applying game elements in learning contexts, with the aim of engaging and motivating students to actively participate in the educational process. This study aimed to carry out a bibliometric analysis of scientific publications, in the Scopus database, on gamification in history teaching, identifying the evolution of scientific productions on the proposed theme in the last ten years. The present work followed a methodology of bibliometric study, which consists of the mathematical and statistical analysis of literary works in a certain field of knowledge, seeking to identify the academic communities, authors and what leads to research for certain themes. The research is classified as exploratory quantitative, using keywords related to the topic of Gamification in History Teaching as a criterion. 24 publications were found in the Scopus database, covering the period from 2013 to 2022. After the analysis, there was a significant increase in the number of publications on the subject in recent years. Spain is the country that most contributed with publications on the subject, Brazil presented a low number of publications. It is necessary that more research related to gamification in History teaching be carried out, so that one can understand how games can influence the teaching of History.